2003
DOI: 10.1257/000282803769206232
|View full text |Cite
|
Sign up to set email alerts
|

Can Mandated Political Representation Increase Policy Influence for Disadvantaged Minorities? Theory and Evidence from India

Abstract: A basic premise of representative democracy is that all those subject to policy should have a voice in its making. However, policies enacted by electorally accountable governments often fail to reflect the interests of disadvantaged minorities. This paper exploits the institutional features of political reservation, as practiced in Indian states, to examine the role of mandated political representation in providing disadvantaged groups influence over policy-making. I find that political reservation has increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
380
2
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 512 publications
(415 citation statements)
references
References 12 publications
28
380
2
5
Order By: Relevance
“…Such significant effect of female representation on the local tax mix supports previous work illustrating its effects on the composition of public spending (e.g., Pande, 2003;Chattopadhyay and Duflo, 2004;Svaleryd, 2009).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Such significant effect of female representation on the local tax mix supports previous work illustrating its effects on the composition of public spending (e.g., Pande, 2003;Chattopadhyay and Duflo, 2004;Svaleryd, 2009).…”
Section: Resultssupporting
confidence: 84%
“…Finally, the share of women in the executive body of the municipality is included. This follows a number of recent studies indicating that gender is an important indicator of policy preferences (e.g., Lott and Kenny, 1999;Edlund and Pande, 2002;Funk and Gathmann, 2008) and that female representation often significantly affects policy outcomes (e.g., Pande, 2003;Chattopadhyay and Duflo, 2004;Svaleryd, 2009). All previous work on this issue, however, looks at the effect of female representation on the size of the public sector or the composition of public spending.…”
Section: Empirical Modelsupporting
confidence: 67%
“…For a discussion of electoral rules and racial politics in elections in India see Pande (2003). 11 We refer to the United States Department of Justice, Civil Rights Division, Voting Section for further details and reference for this section.…”
Section: Statesmentioning
confidence: 99%
“…When aid is used to support public infrastructure investment (transportation and communications), however, the opposite is true: governments are likely to maintain their own fiscal effort in the provision of these goods. Foster and Rosenzweig (2001) and Pande (2003) have shown that when disadvantaged groups in India-the landless poor and scheduled castes (respectively)-were newly able to elect their own representatives, more government resources flowed towards these disadvantaged groups. However, these increased flows largely took the form of increased access to government jobs and targeted welfare transfers.…”
Section: Politics and Social Servicesmentioning
confidence: 99%